TINGKAT KESESUAIAN FISIK LAHAN UNTUK PERKEBUNAN KOPI DI NAGARI AIE DINGIN KECAMATAN LEMBAH GUMANTI SUMATERA BARAT INDONESIA - ade irma suryani (Jurnal Technopreneur (JTech), 2021)
This study answers research questions about: (1). The depth of the coffee plantation land in Nagari Aie Dingin, Lembah Gumanti District, Solok Regency. (2). The slope of the coffee plantation slope in Nagri Aie Dingin Lembah Gumanti District Solok Regency (3). Soil texture of coffee plantations in Nagari Aie Dingin Lembah Gumanti District Solok Regency (4). Coffee plantation structure in Nagari Aie Dingin Lembah Gumanti District Solok Regency (5). The suitability level of coffee plantation land in Nagari Aie Dingin Kecamatan Lembah Gumanti Solok Regency Type of Research This is a quantitative descriptive study. The sampling of this research was carried out by random technique, as many as 3 research areas. Based on land units obtained from overlapping overley sloping maps, land maps, geological maps, landform maps and land use maps. There are 210 different land units in the study area. Based on field analysis, it was found that the physical characteristics of Nagari Aie Dingin seen from the land unit land suitability level consists of two levels: K2.III.Tomp.Km.Sb land unit included in the land suitability level (accordingly). D2.III.Pb.Km.Ht land unit and D2.1.Qv.Km.Sb land unit are included in the land level (not suitable).